ANALISIS MASALAH KESEHATAN LANJUT USIA BANJAR KERTA BUMI, DESA ADAT SUMERTA KAJA, SUMERTA - Paramurthi, I. A. Pascha; Suadnyana, Ida Ayu Astiti; Widyantari, Desak Putu Resmi; Dewi, Ni Luh Anita Chandra (Jurnal Abdi Insani, 2024)
The elderly are the final stage of the life phase. A person who is categorized as elderly will experience an aging process that will result in changes in organ function, both physical and psychological. The rapid increase in the number of elderly people will be accompanied by the emergence of health problems that will be experienced by the elderly. Health problems experienced by the elderly will cause a decrease in productivity and result in a decrease in the quality of life of the elderly. Health analysis in the elderly is important to be carried out as an early detection effort for the potential for health problems in the elderly. The  purpose of this activity is the hope that all parties can play a role in the early detection of health problems that can be experienced by the elderly so that they can identify the population that is required to undergo additional tests to find out the risk of further diseases. This activity is in the form of  health screening, vital sign examination consisting of blood pressure, pulse, respiratory rate, body mass index, disease history, sleep quality check, physical activity examination and cognitive function examination as well as the provision of appropriate gymnastics and education to maintain their health status. The elderly in Banjar Kerta Bumi are predominantly women with hypertension, obesity, poor sleep quality and moderate physical activity. The elderly in Banjar Kerta bumi, Sumerta Kaja Traditional Village are predominantly detected to have health problems.